Fetal growth and its correlation with level of glycemic control in pregnancy with diabetes: an observational study in tertiary care centre of North India - Sharma, Akanksha; Pandey, Amita; Das, Vinita; Agrawal, Smriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Diabetes in pregnancy is a known risk factor for macrosomia and intensive glycemic control is a well-known strategy to prevent this macrosomia. However, does this tight glycemic control is actually beneficial or is it one of the reasons for small for gestational age babies in these women? Is a clinical enigma. We planned this study to see effects of glycemic control on fetal weight and to answer if tight control is always better. Methods: This prospective observational study was conducted in the department of obstetrics and gynaecology in a tertiary care centre (King George medical university) over a period of one year (June 2017-June 2018). All pregnant women with GDM and pre-gestational diabetes with singleton pregnancy were registered in the study after proper consent, followed up for glycemic control, fetal weight. Antepartum risk factors and complications of diabetes were also noted in these women. Results: Total 88 patients included in the study. Five with pre-gestational diabetes, 83 with GDM. Small for gestational age neonates were seen in 54.1% cases, large for gestational age were seen in 2 cases and rest of neonates were appropriate for gestational age. 89.4% had good glycemic control, 7% had over-zealous glycemic control and 3.5% had under-controlled sugars. Conclusions: The results in the study strongly supported the efficacy of good glycemic control in prevention of LGA/macrosomia. However, optimal glycemic control in third trimester does not guarantee appropriate weight of fetus as incidence of SGA/FGR neonates was fairly high (53.9%) even in good glycemic control group.